PENGARUHEFIKASI DIRI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT BAYU JAYA KUSUMA BALI - Erick Ivan Gian; Ida Bagus Alit Ksama Putra; I Putu Ajie Windu Kertayoga; Risna Haryati; Putri Dwi Novrina; Ni luh Sri Kasih (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2023)
This study aims to examine the effect of: (1) self-efficacy and workplace motivation on employee performance, (2) self-efficacy on employee performance, (3) workplace motivation on employee performance. Research design used in this study is causal quantitative research. In this study, the subjects were employees at PT Bayu Jaya Kusuma Bali and the objects of research were self-efficacy, workplace motivation and employee performance. Total population in this study was 117 employees of PT Bayu Jaya Kusuma Bali, and the sample was 54 people. Data was collected by interviews, document recording and questionnaire methods, and then analyzed by multiple regression analysis. The results showed that: (1) self-efficacy and workplace motivation have a significant effect on employee performance, (2) self-efficacy has a significant effect on employee performance, (3) workplace motivation has a significant effect on employee performance.